SUBSIDIES Show MyKad when buying petrol - Nor Azhar, Ahmad (New Straits Times Press (M) Bhd., 2023)
THERE is need to reevaluate the fuel subsidy scheme. A system to monitor and prevent the wasteful dispersal of subsidies is long overdue.